On the recognition of varieties in the grammitid fern genus Melpomene (Polypodiaceae) - Lehnert, Marcus (Phytotaxa, 2013)
In a recent revision of the genus Melpomene several wide-spread species have been recognized to display a greater morphological variability than their congeners. In order to facilitate the discussion of the regional variability, several varieties are here newly described: Melpomene flabelliformis var. tepuiensis from the Guyana Highlands; M. moniliformis var. adnata from Central America and the northern Andes; M. moniliformis var. minor, a dwarfed form occurring throughout the range of the species; M. moniliformis var. subdicarpa from southeast Brazil; M. pilosissima var.tsatchelae occurring throughout the range of the species; M. xiphopteroides var. acrodontia from Bolivia and southeast Brazil.